Distribution pattern of the Persian leopard (Panthera pardus saxicolor) in Iran. - Sanei, Arezoo; Hussin, Mohamed Zakaria (2011)
This study is a new attempt to identify the latest distribution pattern of the Persian leopard (Panthera pardus saxicolor Pocock 1927) in its entire range in Iran. Furthermore, the paper aimed to analyse the climatic factors in the current range of the leopard in the country. The study was performed in 138 sites (56 protected areas, 34 non-protected areas and 48 meteorology stations) throughout the country for a duration of four years starting in 2002 using rapid survey techniques and collection of secondary data. A total of 74 protected and non-protected areas are reported here as the leopard detection sites in the country. Although leopards have a wide distribution in Iran, results indicate that 69% of them are found in the northern part where a large tract of forests is regarded as one of the most important habitats for leopards in the country. In general, the leopards are mostly found in habitats with 0 to 20 days per year of ice cover and 58% of its identified range in the country have 3,100-3,600 sunny hours per annum. Leopards inhabit a wide range of temperature, i.e. from -23.10 to+49.40 ºC however, they are more often found in areas with temperature of 13 to 18 ºC. The majority (66%) of leopard distribution areas receive more than 200 mm of rain per year. Findings of this research would help the researchers in conducting further regional studies inthe leopard distribution range described in this paper. It is also recommended that occupancy modeling on a regional scale should be conducted where leopards are present.